Business Agreements: Enhanced Investor Protection in Enterprises with Generation Z Consumers - Abbas, Ilham; Putri, Ilma Aulia; Mamonto, Moch. Andry Wikra Wardhana; Aswari, Aan (Al-Adalah: Jurnal Hukum dan Politik Islam, 2024)
The purpose of this research is to examine the form of legal protection in PT Yotta's Investment Model Business Agreement. The research method used is the normative-empirical method, which combines elements of normative law with empirical data. The results show that legal protection for the parties in PT Yotta's investment business model agreement is provided in preventive and repressive forms. Preventive protection is reflected in the contract provisions that regulate the rights and obligations of the parties, providing a strong foundation for the maintenance of justice and security. In addition, repressive protection is facilitated by the dispute resolution procedures set out in the agreement, which include the stages of deliberation to reach consensus and the arbitration process. Based on this research, the need for special attention to law enforcement in dealing with cases based on Sharia economic law or Islamic law is highlighted. This is due to the dominance of legal sources from the Civil Code in the context of this still developing law. It is therefore necessary to improve the understanding and skills of law enforcement agencies in dealing with cases involving the principles of Sharia economic law or Islamic law. Therefore, legal protection in the investment business model for the needs of Generation Z provides a solid framework for security and justice for all parties involved. By considering the preventive and repressive aspects, this research provides insightful insights into the legal protection of investment business models.Â